2004
DOI: 10.1111/j.1532-5415.2004.52066.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Complaints and Objective Memory Impairment in the Vienna‐Transdanube Aging Community

Abstract: About 94% (95% CI=69.8-99.8) of memory-impaired individuals do not complain about memory problems. Subjective memory complaints may not be a useful feature in current diagnostic criteria of mild cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
194
5
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(223 citation statements)
references
References 27 publications
19
194
5
5
Order By: Relevance
“…Consistent with previous research, depressive symptoms and negative cognitive bias were strongly correlated in older adults (Alford et al, 1995;Andrews & Brown, 1995;Beevers & Miller, 2004;Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Jungwirth et al, 2004;La Rue et al, 1996;Pearman & Storandt, 2004;Scocco et al, 2001). Extensive research has found strong associations between depressive symptoms and hopelessness (Alford et al, 1995;Beevers & Miller, 2004), death thoughts (Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Scocco et al, 2001) and low self-esteem (Andrews & Brown, 1995;Brown et al, 1986;) both individually and as part of Beck's negative cognitive triad.…”
Section: Depression and Negative Cognitive Biassupporting
confidence: 69%
See 3 more Smart Citations
“…Consistent with previous research, depressive symptoms and negative cognitive bias were strongly correlated in older adults (Alford et al, 1995;Andrews & Brown, 1995;Beevers & Miller, 2004;Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Jungwirth et al, 2004;La Rue et al, 1996;Pearman & Storandt, 2004;Scocco et al, 2001). Extensive research has found strong associations between depressive symptoms and hopelessness (Alford et al, 1995;Beevers & Miller, 2004), death thoughts (Draper et al, 1998;Forsell et al, 1997;Jorm et al, 1995;Scocco et al, 2001) and low self-esteem (Andrews & Brown, 1995;Brown et al, 1986;) both individually and as part of Beck's negative cognitive triad.…”
Section: Depression and Negative Cognitive Biassupporting
confidence: 69%
“…A number of components influence subjective memory complaints. Researchers generally agree that memory complaints are more frequent in those who are depressed (Jorm et al, 1994;Jungwirth et al, 2004;O'Connor, Pollitt, Roth, Brook, & Reiss, 1990). Although there have been many studies that have investigated the association between depressive symptoms and subjective memory complaints, there is a paucity of studies that have evaluated the association between negative cognitive bias and subjective memory.…”
Section: Associations With Subjective Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…However, older adults often mention day-to-day difficulties in remembering everyday events (e.g. Jungwirth, Fischer, Weissgram et al, 2004;Mol, van Boxtel, Willems & Jolles, 2006), and since older adults' community independence and quality of life may depend in part on the ability to remember typical everyday activities, this is an important form of memory that, unusually, remains largely unstudied. The present research, then, examines older and younger adults' memory for everyday events and measures the effect of retrieval support, in the form of SC photographs captured during those events.…”
Section: Introductionmentioning
confidence: 99%